2009
DOI: 10.1037/a0014593
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of dopamine synaptic activity: Degradation of 50-khz ultrasonic vocalization in rats.

Abstract: Vocal deficits are prevalent and debilitating in Parkinson's disease. These deficits may be related to the initial pathology of the nigrostriatal dopamine neurons and resulting dopamine depletion, which contributes to dysfunction of fine motor control in multiple functions. Although vocalization in animals and humans may differ in many respects, we evaluated complex (50-kHz) ultrasonic mate calls in two rat models of Parkinson's disease, including unilateral infusions of 6-hydroxydopamine to the medial forebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(145 citation statements)
references
References 52 publications
9
134
2
Order By: Relevance
“…13 Typically, we see a reduction in quality of the ultrasonic vocalizations characterized by a reduction of the following quantitative acoustic parameters: bandwidth, peak frequency, duration, and intensity. Figure 6 shows the frequency modulated vocalizations of a rat in the PD model at three different time points: baseline, after induction of PD, and after vocalization training.…”
Section: Representative Resultsmentioning
confidence: 99%
“…13 Typically, we see a reduction in quality of the ultrasonic vocalizations characterized by a reduction of the following quantitative acoustic parameters: bandwidth, peak frequency, duration, and intensity. Figure 6 shows the frequency modulated vocalizations of a rat in the PD model at three different time points: baseline, after induction of PD, and after vocalization training.…”
Section: Representative Resultsmentioning
confidence: 99%
“…[16][17][18] Although it is unlikely that USVs are created by vocal fold vibration, 4 they are similar to human vocalizations in that they require control of airflow, subglottal pressure, and glottal adduction and share some common neural pathways. 19,20 Therefore, rat USVs may be a useful model to study the underlying peripheral and central neural mechanisms of vocal control, as well as the effects of interventions and disease.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, Ciucci and colleagues found that striatal dopamine depletions produced symptoms similar to hypokinetic dysarthria, namely reduced call loudness and bandwidth (Ciucci et al, 2009). Those symptoms can be accounted for by reduced laryngeal and respiratory muscle tone.…”
Section: Dopamine's Effects On Echolocation Pulse Acousticsmentioning
confidence: 99%
“…It remains unclear however if the effects of MPTP on call structure are attributable solely to changes in respiratory drive or whether the drug also degraded the bats' ability to articulate the laryngeal apparatus in a complex way. Ciucci and colleagues speculated that striatal dopamine depletion may have constrained fine sensorimotor processes needed for the articulation of more complex broadband vocalizations in rats (Ciucci et al, 2009). It may also be the case that hypertonic laryngeal conditions similarly interfere with articulatory mechanisms in both bats and humans.…”
Section: Dopamine's Effects On Echolocation Pulse Acousticsmentioning
confidence: 99%
See 1 more Smart Citation